2020
DOI: 10.1002/slct.202002976
|View full text |Cite
|
Sign up to set email alerts
|

Polyoxometalates‐Based Ionic Liquids (POMs‐ILs) for Electrochemical Applications

Abstract: Four Polyoxometalates based Ionic Liquids (POMs-ILs) have been developed and applied in electrochemical studies. In a conventional 3-electrode configuration cell the POM-ILs possess three quasi reversible electron transfers (ET) when compared to the commercially available POM under the same experimental conditions. It is also important to note that they presented bleaching and coloration processes faster than the commercially ones. In this configuration cell, the bleaching times are much higher than the colora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Currently, the electrochemical properties of POMs are particularly investigated. For example, Cruz et al presented new polyoxometalates-based ionic liquids and proved their activity in bleaching and coloration process [ 5 ]. Applications of PBA@POM hybrid (PBA: Prussian blue analogue) presented by Wang in 2019, confirmed their excellent electrocatalytic activity [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the electrochemical properties of POMs are particularly investigated. For example, Cruz et al presented new polyoxometalates-based ionic liquids and proved their activity in bleaching and coloration process [ 5 ]. Applications of PBA@POM hybrid (PBA: Prussian blue analogue) presented by Wang in 2019, confirmed their excellent electrocatalytic activity [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…POM–ILs based on the phosphomolybate anion [PMo 12 O 40 ] 3− and organic imidazolium, pyridinium, and phosphorous cations were prepared and used as electrochromic materials with deep eutectic solvents as electrolytes to design efficient electrochromic devices. 155 Additionally, Mo-based electrodes derived from POM–IL, denoted as N/P-MoO 2 @carbon, were designed and exhibited advanced electrochemical performance. 156 The contents of C, N, P, and the pore geometry of N/P-MoO 2 @carbon networks can be easily tailored by adjusting the precursor's cyano group position, resulting in enhanced lithium storage performance.…”
Section: The Catalytic Application Of Il–mocsmentioning
confidence: 99%
“…The physical, rheological and chemical properties of POM‐ILs can be fine‐tuned by chemical modifications. Their potential has been explored in electrochemical applications [88] as well as in the dissolving and delignification of woody biomass [35] . Many studies have indicated that catalytic conversion of lignocellulosic biomass in POM‐ILs is a promising alternative avenue for fuels or fuel additives [89] .…”
Section: Pom‐ils Catalytic Lignin Conversionmentioning
confidence: 99%